Crime scene investigation issues: present issues and future recommendations - Khairul Osman; Gina Francesca Gabriel; Noor Hazfalinda Hamzah (Penerbit Universiti Kebangsaan Malaysia, 2021)
Crime Scene Investigation is the backbone of any criminal investigation. Expert report generated by Crime Scene Investigators are based on scientific evidence and are reported in a standard form. The content, when published should be reviewed rigorously by its peers. The expert report is a document detailing out how the investigation process of a crime scene was performed. The process of collecting and evidence processing do not only entail identifying, collecting and storing evidences for later analysis but it is a step by step process that is well structured in a document called Standard Operating Procedure (SOP) for Crime Scene Investigator. SOP is a complex document and sometimes overwhelmingly technical for the uninitiated. But if understood, it can be a good guide for law practitioners to determine if a piece of evidence should be included in a case. This article details out the SOP which entails groundwork before entering a crime scene, processing of a crime scene and wrapping up of the crime scene investigation. At each step, this paper will look at how it is adopted in current practices, its weakness and suggested improvement that should be adopted to ensure a final quality expert report.